Changes of Public Sector Human Resource Management (HRM): Trend in pre and post COVID-19 technological revolution - Afzal Sayed Munna; Duratul Ain Tholibon; Giuseppe Cantafio; Ulil Nasiruddin (International Journal of Educational Administration, Management, and Leadership, 2023)
Public sector human resource management is a way to manage human in a hierarchical activity which acts as the main rotor of efficiency and effectiveness of public-scale growth and development. As our environment changed in 2020 caused by covid-19 pandemic, so does the human resource management. Substantial changes in society impacted the way we shape management activity. This study aims to map the research trend changes of public sector human resource management in pre and post covid-19 period. We conduct bibliometric study to explore the factors and criteria of a toxic leader from open access scopus indexed journals using biblioshiny application limited to pre (2016 to 2019) and post (2020 to 2023) covid-19 periods. The criteria for filtering journal articles are based on PRISMA and JBI standards. Data suggested that covid-19 event ignite the research production. The research domains for pre covid-19 were focused on human resource growth and development, while post covid-19 domains were focused on survival and resilient. Country rank of most published paper related to the locus field also related to worldwide survey of economic growth in pre to post covid-19 pandemic. However, rapid increase of publication in post covid-19 period did not followed by study continuity and relatedness.